Temporal Variation of Salinity in the Middle Shatt al-Arab River, Southern Iraq - Salem Abdullah , Prof. Dr. Sadiq (Basra studies journal, 2024)
The Shatt al-Arab River, originally formed by the confluence of the Tigris and Euphrates rivers in Qurna, north of Basra (a situation altered by the cutoff of the Euphrates flow in recent years), passes through Basra’s lands and serves as the primary source of water for various purposes. Presently, the Shatt al-Arab faces significant water quality degradation due to reduced freshwater inflows, tidal influences that allow seawater intrusion upstream, and pollution. Given that Basra's city center has a high population density and heavy dependence on the river's water, it was chosen as the focus of this study. The research examined salinity fluctuations through continuous hourly measurements over several months from 2018 to 2020. Findings indicate that temporal factors significantly influence salinity variations, with changes occurring annually, monthly, daily, and even hourly. These temporal changes are closely linked with freshwater discharge levels and tidal movements, shaping salinity patterns in the middle section of the Shatt al-Arab River.